(untitled) (Research, Society and Development, 2020)
In response to the unsustainable development in indigenous communities, which does not improve their living conditions and threatens their native culture, the aim of the present study is to analyze local development and the living conditions of the Catu indigenous community, located between Goianinha and Canguaretama, in Rio Grande do Norte state, Brazil. To that end, the knowledge of the indigenous people regarding the problems and solutions related to sustainability was relied upon. This qualitative research investigated the living conditions of the native people and the solutions to the problems they proposed using the tools of the Participatory Rural Appraisal method. The results of the study in Catu showed that the participants of the appraisal were fully aware of the community’s potentials and problems. Despite the potentials described by the indigenous people, there are problems such as low education level; absence of land demarcation, technical assistance and help from the producer cooperative; inadequate disposal of solid wastes; poor access roads and most importantly, the socioenvironmental pressure caused by the commercial planting of sugarcane and current urbanization, both of which threaten sustainability. With a view to introducing more sustainable strategies, a community action plan against exogenous actions was formulated. Given the indigenous customs, these actions are unsustainable because they endanger the lives and traditions of the community, in addition to their right to a long and prosperous life in their own land.